1974 ネン ノ ナンキョクサン ヤマトインセキ ノ タンサ ト サイシュウ - 矢内, 桂三; ヤナイ, ケイゾウ; YANAI, Keizo (国立極地研究所, 1976)
P(論文) From October 25, 1974 to January 17, 1975 a four-man party of the 15th Japanese Antarctic Research Expedition (1973-1975) made an oversnow traverse to the Yamato Mountains area for a systematic search for the Yamato meteorites and geological survey. A total of 663 meteorites were collected in November and December 1974, revisiting the sampling area in 1969 and 1973 and searching extensively the Meteorite Ice Field area surrounding the Yamato Mountains. In addition to research activities mechanisms of meteorite accumulation and the relations between moraines and meteorites are discussed. departmental bulletin paper